Historical empathy in the paradigm of social studies teachers in Palembang City - Aderoben, Andromeda; Darmawan, Wawan (Prodi Pendidikan Sejarah Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Sumatera, 2024)
This research is based on the need to address the lack of historical empathy in Indonesia through social studies education. It highlights the importance of promoting the concept of historical empathy, which is currently not widely recognized in the country. The study focuses on the perspectives of 15 junior high school social studies teachers in Palembang City regarding historical empathy. Data was collected through questionnaires, with respondents answering various questions about historical empathy, including its definition, significance, relevant topics, suitable learning resources, methods, challenges faced, and recommendations for teaching it effectively. The findings indicate that there are misconceptions among teachers regarding historical empathy, particularly in distinguishing it from sympathy and understanding its psychological and historical aspects. Despite these challenges, the teachers acknowledge the importance of integrating historical empathy into social studies education. This research provides a foundational understanding of teachers' perspectives on historical empathy in Indonesia.